Multi-Tiered Culturally Responsive Behavior Support: A Qualitative Study of Trauma-Informed Education in an Australian Primary School - Schimke, Dayna; Krishnamoorthy, Govind; Ayre, Kay; Berger, Emily; Rees, Bronwyn (Frontiers in Education, 2022)
There is growing awareness of the impact of inter-generational trauma and community disadvantage on the educational achievement of Aboriginal and Torres Strait Islander (First Nations) children. Scholars have pointed to the need for culturally responsive and trauma informed approaches to complement existing disciplinary and behavior support practices utilized in schools. This pilot research explored the experiences of primary school teachers who were supported to implement trauma informed practices in a regional primary school with a high number of students of First Nations descent. Qualitative interviews with eight teachers were conducted after a three-year (2017-2020) implementation of the Trauma Informed Behavior Support (TIBS) program. Using a thematic analysis approach, the study identified the following themes: changes in teacher knowledge about the impact of inter-generational trauma, acknowledgement of the multi-systemic influences on student behavior difficulties, increased self-efficacy in providing culturally safe learning environments and strategies for building relationships with First Nations students. The findings offer insights into factors that support the successful and sustainable implementation of culturally responsive and trauma informed practices in primary school settings.